2022
DOI: 10.1002/brb3.2407
|View full text |Cite
|
Sign up to set email alerts
|

A neural signature for combined action observation and motor imagery? An fNIRS study into prefrontal activation, automatic imitation, and self–other perceptions

Abstract: Introduction: Research indicates that both observed and imagined actions can be represented in the brain as two parallel sensorimotor representations. One proposal is that higher order cognitive processes would align these two hypothetical action simulations. Methods:We investigated this hypothesis using an automatic imitation paradigm, with functional near-infrared spectroscopy recordings over the prefrontal cortex during different motor simulation states. On each trial, participants (n = 14) observed a pictu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 140 publications
(231 reference statements)
2
10
0
Order By: Relevance
“…This index explains that AOMI activates more neural involvement and functioning. Thus, our research indirectly supports Emerson et al. ’s ( 2022 ) hypothesis and advances our knowledge in this line of scientific endeavors.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…This index explains that AOMI activates more neural involvement and functioning. Thus, our research indirectly supports Emerson et al. ’s ( 2022 ) hypothesis and advances our knowledge in this line of scientific endeavors.…”
Section: Discussionsupporting
confidence: 79%
“…Recent neurophysiological research ( e.g. , Eaves et al, 2016 ; Emerson et al., 2022 ) showed that when combining AOMI, it activates more motor cortical activities than pure AO or MI. The combination of AOMI allows the motor cortex to have a better function to plan, control, and execute the voluntary movement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations